Estudio de factibilidad técnico-financiero para un piloto de inyección de agua in-fill, en Campo Maduro de la cuenca del Valle Superior del Magdalena mediante simulación de yacimientos (2017)
The method of water injection is used worldwide to extract the remaining crude in the deposits, after the primary production stage has come to an end. The injection of water in a strategic way in the structure of the reservoir, in symmetry with the existing wells, improves the efficiency of sweeping and reduces the water cut at the same time that it achieves a repressurization of the deposit inducing to a greater recovery of Raw. The production in the North block of the Mature Field has been characterized by being complicated, because the site has been depressurized quickly as it is exploited, added to it being classified as a subnormal pressure deposit with a small initial layer of Gas and a low-pressure aquifer, which serve as primary production mechanisms; The block is separated from the rest of the field by a non-sealing contact of failure.